Intestinal healing in rats submitted to ethanol ingestion - Pereira,Rodrigo Severo de Camargo (2012)
PURPOSE: To study the effect of alcoholism on intestinal healing and postoperative complications in rats METHODS: One hundred and sixty rats were divided into two groups: control and treated. The control group received water and the treated group 30% ethanol. After 180 days, colotomy with anastomosis were performed. After, the groups were divided into four subgroups: 20 rats for study at the following moments: 4th, 7th, 14th and 21st postoperative. The analyzed parameters were: weight gain, breaking strength, tissue hydroxyproline, postoperative complications and histopathological study RESULTS: Weight gain was greater in the control group (p<0.05). When all the subgroups were clustered, breaking strength was significantly greater in the control (p<0.05). Histopathology and hydroxyproline dosage did not show differences. There were five surgical site infections in the treated group while the control group showed two (p>0.05). Nine fistulas occurred in the treated group whereas the control group two (p<0.05). There were three deaths in the control group and seven in the treated group (p>0.05). CONCLUSIONS: Treated group undergo a malnutrition process that is revealed by lower weight gain. Impaired intestinal healing as indicated by smaller breaking strength. There were a larger number of postoperative complications in the treated animals.